2024
DOI: 10.1001/jamanetworkopen.2024.11127
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Web-Based Cognitive Behavioral Self-Help Intervention for Binge Eating Disorder

Luise Pruessner,
Christina Timm,
Sven Barnow
et al.

Abstract: ImportanceBinge eating disorder (BED) is one of the most frequent eating pathologies and imposes substantial emotional and physical distress, yet insufficient health care resources limit access to specialized treatment. Web-based self-help interventions emerge as a promising solution, offering more accessible care.ObjectiveTo examine the effectiveness of a web-based cognitive behavioral self-help intervention for individuals with BED.Design, Setting, and ParticipantsThis 2-arm, parallel-group randomized clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…There is a growing scientific literature supporting the use of online interventions to treat people with eating disorders characterised by recurrent binge eating. Previous studies in this field have shown the efficacy of online self-help CBT interventions in reducing binge eating and improving mental health in people with binge/purge eating disorders or BED [54,55]. For instance, a recent RCT found that a 12-week online self-help CBT program that used exercises addressing risk factors for and the mechanisms of BED reduced binge eating, eating disorder psychopathology, emotion dysregulation, depression, and anxiety in people with BED [55,56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing scientific literature supporting the use of online interventions to treat people with eating disorders characterised by recurrent binge eating. Previous studies in this field have shown the efficacy of online self-help CBT interventions in reducing binge eating and improving mental health in people with binge/purge eating disorders or BED [54,55]. For instance, a recent RCT found that a 12-week online self-help CBT program that used exercises addressing risk factors for and the mechanisms of BED reduced binge eating, eating disorder psychopathology, emotion dysregulation, depression, and anxiety in people with BED [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in this field have shown the efficacy of online self-help CBT interventions in reducing binge eating and improving mental health in people with binge/purge eating disorders or BED [54,55]. For instance, a recent RCT found that a 12-week online self-help CBT program that used exercises addressing risk factors for and the mechanisms of BED reduced binge eating, eating disorder psychopathology, emotion dysregulation, depression, and anxiety in people with BED [55,56]. The findings of the current RCT contribute to the literature in this field by showing that online treatments based on CBT or HAPIFED delivered in a group therapy format via videoconferencing are also an effective treatment option to assist people with BED.…”
Section: Discussionmentioning
confidence: 99%
“…Possibly reducing the barriers of face-to-face treatments by being more flexible, accessible, and cost-efficient, web-based interventions have been developed to complement established therapies and are increasingly integrated into routine care settings . While meta-analyses suggest that web-based interventions may reduce eating disorder symptoms, there is a scarcity of research investigating treatments tailored to BN, and previous studies are often limited regarding their generalizability to clinical practice .…”
Section: Introductionmentioning
confidence: 99%
“…Possibly reducing the barriers of face-to-face treatments by being more flexible, accessible, and cost-efficient, web-based interventions have been developed to complement established therapies and are increasingly integrated into routine care settings. 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 While meta-analyses suggest that web-based interventions may reduce eating disorder symptoms, there is a scarcity of research investigating treatments tailored to BN, and previous studies are often limited regarding their generalizability to clinical practice. 17 , 18 , 19 , 20 , 24 , 25 , 27 Therefore, more research is needed to evaluate the effectiveness of web-based interventions targeting patients diagnosed with BN, especially when applied in naturalistic settings.…”
Section: Introductionmentioning
confidence: 99%